PANI/MWCNT based humidity sensor - Humud, Hammad R. (Iraqi Journal of Physics, 2019)
Polyaniline Multi wall Carbon nanotube (PANI/MWCNTs) nanocomposite thin films have been prepared by Plasma jet polymerization at low frequency on glass substrate with preliminary deposited aluminum electrodes to form Al/PANI-MWCNT/Al surface-type capacitive humidity sensors, the gap between the electrodes about 50 μm and the MWCNTs weight concentration varied between 0, 1, 2, 3, 4%. The diameter of the MWCNTs was in the range of 8-15 nm and the length 10-55 μm. The capacitance-humidity relationships of the sensors were investigated at humidity levels from 35 to 90% RH. The electrical properties showed that the capacity increased with increasing relative humidity, and that the sensitivity of the sensor increases with the increase of the additive (MWCNTs); while each of the response time and the recovery time increasing with concentration. The change in MWCNTs concentration leads to a change in the energy gap as well as the initial capacity. The capacitance increases linearly with the relative humidity at MWCNTs concentration of 3% for thus the possibility of manufacturing humidity sensor with good specifications at this concentration.